PENGARUH SENAM PROLANIS TERHADAP PENGENDALIAN TEKANAN DARAH DAN KADAR GULA DARAH PADA PASIEN PENYAKIT KRONIS DI PUSKESMAS LUBUK BAJA KOTA BATAM - Andi Ipaljri Saputra; Muhammad Azmi Fanany; Istiqa Syaraya Putri (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Non-Communicable Diseases (NCDs) such as hypertension and Type 2 Diabetes Mellitus (DM) are major causes of mortality globally and in Indonesia. Batam City, particularly at the Lubuk Baja Public Health Center (UPT Puskesmas Lubuk Baja), has reported a relatively high prevalence of these chronic diseases. The Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis/Prolanis) initiated by BPJS Kesehatan, including Prolanis exercise, represents a non-pharmacological strategy aimed at controlling blood pressure and blood glucose levels. Methods: This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 88 chronic disease patients participating in the Prolanis program at Lubuk Baja Public Health Center, Batam City, in 2025, selected using purposive sampling based on inclusion and exclusion criteria. Blood pressure and blood glucose levels were measured before and after the Prolanis exercise intervention. Data were analyzed using univariate and bivariate analyses with the Paired T-Test. Results: The results of the paired t-test demonstrated a significant effect of Prolanis exercise on blood pressure control with a p-value of 0.000 (p < 0.05), and on blood glucose control with a p- value of 0.000 (p < 0.05). Conclusion: There is a significant effect of Prolanis exercise on controlling blood pressure and blood glucose levels among patients with chronic diseases at Lubuk Baja Public Health Center, Batam City, in 2025. Keywords: Prolanis Exercise, Blood Pressure, Blood Glucose Level, Chronic Disease